(untitled) (Fiep Bulletin - online, 2014)
In Santa Maria City - RS, the Integrated Center of Study and Support to the Old Age works for more than 20 years with "groups of physical activities" in project which keeps elderly people in their districts and more than 65 groups, both urban and rural, from which 20 groups were selected to this research, considering criteria such as antiquity, number of participants and social visibility. This study aims to approach Santa Maria city as a place of construction of human getting old. Among the results obtained until this moment, it is highlighted the profile of the groups of the coordinators of living: they are around 55 to 72 years old, 55% of them studied only elementary school, 90% of these coordinators considered themselves catholic, and 20 % of them are already coordinators for more than 6 years. In relation to the places, the groups have adequate places, which are ample and illuminated and with facilitated entrance, being almost always in saloons of the churches. The contents taught are predominantly the gymnastic, in their different ways, besides the recreative activities and dance in a less proportion. It is possible to conclude that it is important to invest in the gerontologic education of the university students in order to promote critical readings of the processes of getting old. We could also conclude that, according to the collective reports, that old people of the groups are aware of the importance of the project, reinforcing that, since it creation, it has been gradually built a new possibility to get old in Santa Maria.